The influence of different root canal open access shapes on the use of rotary root canal enlargement - Ta-Ya Hou; Chuan-Yi Kao; Chia-Tze Kao; Tsui-Hsein Huang (Elsevier, 2024)
Background/purpose: The success of root canal treatments is influenced by the shape of the access opening and the outcomes of root canal enlargement. The aim of this study was to evaluate the impact of various rotary instruments on the maintenance of the root canal's central alignment post shaping, considering a range of access cavity designs. Materials and methods: Using digital tooth simulation, 4 sets of 12 teeth underwent traditional (TradAC) or conservative (ConsAC) access cavity preparations. Root canals were enlarged with TruNatomy or ProTaper Ultimate rotary instruments. Canal transportation and centering ratio were separately measured. Statistical analysis was performed using JMP trial 17 software. Results: The analysis revealed no significant difference in buccal and lingual canal transportation among different rotary instruments or canal enlargement designs (P > 0.05). TradAC yielded higher centering ratios in MB and ML canals, while ConsAC excelled in the distal canal for the TruNatomy group. Conversely, in the ProTaper Ultimate group, ConsAC demonstrated higher ML canal ratios (P < 0.05). Conclusion: TruNatomy maintained superior canal centering with ConsAC, while ProTaper performed better with TradAC.